Effectiveness of the Digital and Technological Entrepreneurship Ecosystem in Cameroon - Dombou, Dany R. T.; Ewane, Cybele (Archives of Business Research, 2022)
This study aims to investigate the factors associated with the effectiveness of the technological and digital entrepreneurship ecosystem (ECOTECH) in Cameroon. The methodology adopted consists of a range of semi-structured interviews in the ecosystem stakeholders. This was followed by a Pearson correlation analysis of a questionnaire submitted to 117 start-ups. The main results indicate that, the Cameroonian ECOTECH is a young and weakly effective environment. As far as start-ups are concerned, administrative difficulties, the distraction effect (increased involvement in activities not directly related to that of the start-up), and the lack of professionalism are closely linked to their ineffectiveness. Regarding the role of the state, start-ups value at 42.52% effective the efforts made by the government in improving the regulatory framework. The prevalence of the informal sector and the lack of infrastructure are among the reasons of this result. Regarding the role of incubators, although they have limited financial means to carry out their actions, start-ups rate their effectiveness at 63.5%. This result can be explained, among other things, by the interest for start-ups in the technical support and lobbying offered by incubators